Influence of multiple variables on characteristics of “Neurobionanoparticles” prepared by diffusion-solvent-evaporation technique - Mansor, Nur 'Izzati; Doolanea, Abd Monem; Wan Mohd Azam, Wan Imtiyaz; Abdul Latip, Siti Suhaila; Yusof, Nurul Amirah; Mohamed, Farahidah (2012)
We had attempted to synthesize nanoparticle called “Neurobionanoparticle” (NBP), consisted of biodegradable polymers (PLGA and chitosan) and plant-origin material (Nigella Sativa), intended for delivery of plasmid DNA to the central nervous system (CNS). Several independent variables were employed namely, type of co-solvents (ethyl acetate, acetone and chloroform), concentration of N. sativa (0.3 %, 0.6%, 0.9% and 1.2 % v/v), concentration of chitosan (1% and 2% w/v) and homogenization speed of primary and secondary emulsion formation (8 000, 11 500 and 20 500 rpm). Size, zeta potential and surface morphology of the particles were characterized as a function of those multiple variables. The results suggested that fabrication of NBP using the diffusion-solvent-evaporation method employing ethyl acetate as co-solvent and speed 20 500 rpm successfully produced spherical nanoparticles with particle size of around 300 nm. At 2% w/v chitosan, high concentration of N. sativa (1.2% v/v) was found to moderately reduce the size of the nanoparticles to 200 nm. As a conclusion, appropriate set of variables could be employed to yield NBP of desirable characteristics.